Utilization of Technology as a Strategy to Improve Teacher Performance and Quality of Education in Elementary Schools - Meliyani, Hani; Ristiyani, Iis; Lisnawati, Elis; Kanya, Nita (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2025)
The improvement of education quality requires teachers to utilize technology in learning. However, not all teachers can optimize technology effectively, which may impact their performance. This study aims to analyze the effect of technology utilization on teacher performance at SDN 1 Babakanmulya. The research method used is quantitative with a descriptive approach. Data were collected through questionnaires distributed to 10 teachers and analyzed using IBM SPSS version 25. The results show that teachers' technology utilization falls into the moderate category, with an average score of 65.230 and a standard deviation of 3.798. Meanwhile, teacher performance is also mostly in the moderate category, with an average score of 64.120 and a standard deviation of 4.255. A simple linear regression test indicates that technology utilization significantly influences teacher performance (p = 0.000 < 0.05), with the regression equation Y = 4.075 + 0.896X. The coefficient of determination (R²) of 0.703 indicates that 70.3% of the variability in teacher performance is explained by technology utilization, while 29.7% is influenced by other factors. Based on these findings, it can be concluded that technology utilization significantly affects teacher performance, emphasizing the need for improving teachers' technological competence through training and professional development